Reconfiguring Religious Authority in the Digital Age: an Analysis of Lay Preaching in Indonesian Muslim Society - Ardiansyah, Al Fiqri; Tambunan, Marhamah Annazah; Muttaqin, Fakih Fadilah; Ashani, Sholahuddin (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article analyzes the reconfiguration of religious authority within the Indonesian digital ecosystem thru a study of three non-traditional da'wah figures: Syifa Nurfadhilah, Ning Umi Laila, and Akri Patrio. The three represent a new model of religious authority not based on scholarly lineage or formal institutions, but rather formed thru digital performativity, emotional narratives, and the active engagement of audiences on social media. This research uses a qualitative approach with digital content analysis and a study of audience interaction in the comment section as the primary data. The research findings indicate that religious legitimacy now operates as